2010
DOI: 10.1080/07448480903380300
|View full text |Cite
|
Sign up to set email alerts
|

Pregaming: An Exploratory Study of Strategic Drinking by College Students in Pennsylvania

Abstract: Pregaming presents a growing challenge for campus officials. Additional research is needed on the nature of the problem and which combination of prevention strategies might best address this behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
101
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(115 citation statements)
references
References 5 publications
11
101
3
Order By: Relevance
“…Pre-loading has been found to be common with one small (n = 112) US study finding 64.3% of participants had drunk alcohol prior to attending an event or social activity in the past two weeks. The amount consumed during pre-loading sessions predicted the expectancies of consumption later in day [30]. Similarly, a larger study of young adult bar patrons in the US (n = 1040) found pre-loading to be common among college populations, to be similar for males and females and to be associated with intentions to drink [31].…”
Section: Discussionmentioning
confidence: 97%
“…Pre-loading has been found to be common with one small (n = 112) US study finding 64.3% of participants had drunk alcohol prior to attending an event or social activity in the past two weeks. The amount consumed during pre-loading sessions predicted the expectancies of consumption later in day [30]. Similarly, a larger study of young adult bar patrons in the US (n = 1040) found pre-loading to be common among college populations, to be similar for males and females and to be associated with intentions to drink [31].…”
Section: Discussionmentioning
confidence: 97%
“…22 Although there is evidence that pregaming in high school is a risk factor for heavier alcohol use in college, 22 research on pregaming has not yet reported how this style of drinking changes during the critical first weeks of college. Given the disparity in pregaming rates between high school and college, 18,19,22,23 pregaming clearly escalates at some time, but it is unclear when this change occurs. There is evidence that pregaming starts to increase in the summer between high school graduation and college entry, 24 but there are insufficient data to examine how pregaming changes during the first weeks of college or whether there are differences in drinking behaviors and consequences for students who initiate pregaming upon college entry relative to those who have high school experience.…”
mentioning
confidence: 97%
“…20 For example, one study found that students who pregame ingest over 3 drinks in about an hour and typically use hard alcohol. 19 They also consume more alcohol on occasions where pregaming is involved than occasions where they refrain from pregaming. 17,19,21 Not surprisingly, this style of consumption has been linked to more severe consequences relative to drinking without pregaming, including higher scores on the Rutgers Alcohol Problem Inventory (RAPI), 19 greater blood alcohol concentration (BAC) per drinking occasion, 17,21 and receiving alcohol-related policy violations on campus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is scope for future work to consider the type of drinking games to examine whether socially anxious individuals are at greater risk of participating in structured games that provide more certainty, and the role of coping motives in choosing to participate in different types of games. Given that socially anxious individuals may drink prior to a social event to reduce anticipatory anxiety (70,71), future research may also consider the role of pre-drinking in the relationship of social anxiety and frequency of drinking game participation.…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%